PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT RAFFLY HDPE INDONESIA - Muhammad Naufal; Kadarmanta Kadarmanta (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to examine the extent to which job stress and the work environment influence employee performance at PT Raffly HDPE Indonesia. A quantitative approach was applied, involving 62 respondents who completed a structured questionnaire. The data were analyzed using simple and multiple linear regression with SPSS version 26. The analysis revealed that job stress significantly affects employee performance, demonstrated by a t-value of 10.645 exceeding the critical value of 1.988, with a significance of 0.000. The work environment also shows a significant effect, reflected by a t-value of 12.639 and a significance level of 0.000. Simultaneously, both variables exert a significant influence on employee performance, indicated by an F-value of 104.134 with a significance of 0.000. The R Square value of 0.779 shows that 77.9% of the variation in employee performance is explained by job stress and the work environment, whereas the remaining percentage is influenced by other factors. Keywords: Job Stress, Work Environment, Employee Performance.